ADAPTATION OF MSMEs BUSINESS IN NEW NORMAL CONDITIONS WITH THE IMPLEMENTATION OF STANDARD HEALTH PROTOCOLS - Nuryanti Taufik; Andina Eka Mandasari; Dewi Permata Sari; Epi Dani Harison (LPM Universitas Pasundan, 2021)
2020 is a tough year for all people in the world, including Indonesia. This is due to the emergence of a new virus called Covid-19. In order to avoid a wider spread of the virus, the Indonesian government adopted the PSBB or Large-Scale Social Restrictions policy, one of which limits direct contact between humans. One of the business sectors affected by this policy is MSMEs, where business is daily in nature and relies heavily on direct interaction. After almost two months of implementing the PSBB in Indonesia, the government finally announced a new condition for Indonesia, namely